Wavelength-Tuneable Near-Infrared Luminescence in Mixed Tin–Lead Halide Perovskites - Liu, Meiyue; Zhao, Ru; Sun, Fuhao; Zhang, Putao; Zhang, Rui; Chen, Zeng; Li, Shengjun (Frontiers in Chemistry, 2022)
Near-infrared light-emitting diodes (NIR-LEDs) are widely used in various applications such as night-vision devices, optical communication, biological imaging and optical diagnosis. The current solution-processed high-efficiency perovskite NIR-LEDs are typically based on CsPbI3 and FAPbI3 with emission peaks being limited in the range of 700–800 nm. NIR-LEDs with longer emission wavelengths near to 900 nm can be prepared by replacing Pb with Sn. However, Sn-based perovskite LEDs usually exhibit a low efficiency owing to the high concentration of Sn-related defects and the rapid oxidation of Sn2+ to Sn4+, which further induces the device degradation. These problems can be solved by rationally adjusting the ratio between Pb content with Sn. Mixed Sn-Pb halide perovskites with a smaller bandgap and superior stability than pure Sn-based perovskites are promising candidates for manufacturing next-generation NIR emitters. In this study, we systematically investigated the optical properties of a family of hybrid Sn and Pb iodide compounds. The emission spectra of the mixed Sn-Pb halide perovskites were tuned by changing the Sn:Pb ratio. Consequently, the peak emission wavelength red-shifted from 710 nm to longer than 950 nm. The absorption and photoluminescence emission properties associated with different compositions were compared, and the results demonstrated the potential of MA- and FA-based mixed Sn-Pb halide perovskites for preparing low-cost and efficient NIR-LEDs. In addition, we clarified the influence of cations on the bandgap bowing effect and electronic properties of mixed Sn-Pb halide perovskites.